미디어스킨 기반의 그래픽 조형 요소에 관한 연구 - 김문석; 오문석; Kim, Moon Seok; Oh, Moon Seok ((사)디지털산업정보학회 논문지, 6(3), 2010)
Media Skin is in form extended of TV or computer monitor that is digital media picture or digital output of graphic. Mean reflex or graphics applied in LCD Window of portable phone or LED display etc. of city environment mainly. Draft and study skill development trend and studied about role as graphic modeling to Media Skin. Media Skin that inflect LED over inside and outside of the country impulse to steal current is embodied. It is situating from modern society to one media trend. Progressed general investigation about Media Skin's connection skill in research. As culture contents progressed determinate research to graphic modeling element etc. As graphic modeling of new media special quality is construed by 4 as following. Contact, Real time, Nonlinear, Multi-Communication are it. Media Skin has function as symbol of city or media construction facade. Also, have enough value as function new media as information offer function, art.